Review of the Brazilian species of Physiculus (Gadiformes: Moridae), with description of a new species from Saint Peter and Saint Paul Archipelago, equatorial Atlantic - Pires, Alessandra M. A.; Carvalho-Filho, Alfredo; Ferreira, Rômulo C. P.; Viana, Danielle; Nunes, Diogo; Hazin, Fabio H. V. (Zootaxa, 2019)
Three valid species of the genus Physiculus are known from the Brazilian marinewaters. A fourth, new species, Physiculus cirm n. sp.., is described based on seventeen specimens collected in the surroundings of Saint Peter and Saint Paul Archipelago, equatorial Atlantic. A review of the Brazilian species of Physiculus is provided, as well as a key to the species of the genus reported from the Atlantic Ocean. The new species is distinguished from all its congeners, except P. cynodon and P. karrerae, by the large number of longitudinal series of scales (156–189 vs. 70–150). P. cynodon from the Northern Pacific has about 200 longitudinal series of scales, and it differs from the new species by the number of rays of the first dorsal fin (6–8 vs. 10 in P. cynodon), pectoral-fin rays (20–25 vs. 27 in P. cynodon), and the presence of an outer row of large canine teeth on upper and lower jaw. From P. karrerae, which has 134–160 longitudinal series of scales, the new species differs by the presence of scales on the tip of the snout and dorsal-fin membrane, and the number of pectoral-fin rays (20–25 vs. 24–27 in P. karrerae). [Zoobank URL: urn:lsid:zoobank.org:act:1AFBC251-2BB1-4479-98A4-307188EC5D66]